AB0942 Effect of corticosteroid infiltrations on diabetes. a monocentric retrospective study. (15th June 2017) - Mathieu, S; Couderc, M; Tatar, Z; Lopez, J; Malochet-Guinamand, S; Dubost, J-J; Tournadre, A; Soubrier, M
Abstract : Background: Corticosteroid therapy can unbalance diabetes, particularly when administered orally, but also during articular infiltration. Corticosteroid infiltrations are an integral part of the therapeutic arsenal in rheumatology. They are utilized to treat congestive articular flare-ups of osteoarthritis or inflammatory rheumatic diseases. Periarticular or ductal pathologies, such as trochanteric bursitis, rotator cuff pathology and carpal-tunnel syndrome, may require the use of these infiltrations. Caution is often required when using corticosteroid infiltrations in diabetics. Objectives: The purpose of our study was to evaluate whether or not diabetic patients undergoing a corticosteroid infiltration during hospitalization had a diabetes imbalance. Methods: Diabetic patients having undergone a corticosteroid infiltration during hospitalization between 2009 and 2015 were sought. We collected data regarding their rheumatological pathology, glycated hemoglobin (HbA1c), and fasting glycemia on the day of the infiltration, the next day and after 48 hours. Results: A total of 114 patients were included in our study. The average age was 72.1±9.4 years. All of them had Type 2 diabetes, and 35 of them were treated with insulin. Average HbA1c was 7.3±0.1%. Overall, 47 (41.2%) patients had an HbA1c below 7%. A total of 31 (27.2%) patients had a diabetes imbalance after infiltration, and 19 of these, who were taking oral antidiabetics, required 48 hours of rapid insulin to balance their glycemia. Overall, 12 patients increased their insulin dose. Out of the 47 patients with good HbA1c, 7 (14.9%) of them had a glycemia imbalance, versus 24 (35.8%) who were unbalanced out of the 67 patients whose HbA1c exceeded 7% (p=0.013). Conclusions: Corticosteroid infiltrations can lead to a diabetes imbalance, thus making it necessary to administer a few days of rapid insulin or to increase the insulin dose. A patient whose HbA1c is below 7% has a low risk of unbalancing his/her diabetes after corticosteroid infiltration. Disclosure of Interest: None declared